Pengaruh Literasi Keuangan Dan Pendidikan Keuangan Di Keluarga Terhadap Perilaku Manajemen Keuangan Mahasiswa Dengan Locus Of Control Sebagai Variabel Moderasi - Fridolin Jesika Jehamin (Yayasan Literasi Ilmiah Indonesia, 2024)
Purpose: This research aims to determine and analyze the influence of financial literacy on students' financial management behavior, to determine and analyze the influence of financial education in the family on students' financial management behavior, to determine and analyze the influence of locus of control on students' financial management behavior, to determine the role of locus of control. control in moderating financial literacy on student financial management behavior, to determine the role of locus of control in moderating financial education in the family on student financial management behavior. Method: The approach used in this research is a quantitative approach. The research took samples from Accounting Study Program students at several campuses in the Special Region of Yogyakarta. The primary data obtained in this research are the results of questionnaires obtained from respondents and then processed using SPSS with multiple linear regression analysis Finding: The research results show that Locus of Control has a positive and significant effect on Financial Literacy and Family Financial Education (Moderating). Based on the results, the significance obtained for 0.026 and 0.02 is 0.00, so it can be stated that the Locus of control variable moderates the variables X1 and X2. These results show that the locus of control variable is able to moderate the relationship between student financial literacy and student financial management behavior. Novelty: : This research is important to carry out because previous research shows different results that influence students' financial management behavior and there is also a phenomenon among students with high levels of consumption and can be influenced by the surrounding environment in terms of students' financial behavior.